(untitled) (Community Based Medical Journal, 2025)
The angle of the mandible is a bony prominence situated between the ramus and the body of the mandible, and is formed by the junction of the horizontal and vertical planes of the mandible. It is an important structure in the head neck region that is often used as a reference point for various surgical procedure. A cross-sectional, descriptive study was done in the Department of Anatomy, Mymensingh Medical College, Bangladesh, between July 2019 to June 2020, to measure various mandibular angles. A non-random purposive sampling technique was adopted. A total of 150 fully ossified dry human mandibles were collected. The mandibular angle is formed by the line tangent to the lower border of mandible and the line tangent to the distal border of ascending ramus and the condyles. The angle was recorded by goniometer. One arm of a transparent goniometer was placed along the base of mandible and other arm on the line touching the posterior most point on condyles and posterior border of ramus on both sides. The mean±SD angle of the mandible on right side was 125.56º±6.5º and on the left side was 125.69º ±6.5º. The mandibular angle on the both sides ranged between 110° and 142°. The observations of this study have a greater impact on reconstructive surgeries of angle of mandible like augmentation or reduction, fracture fixation as well as forensic odontology. CBMJ 2025 July: vol. 14 no. 02 P:48-51